DIMENSI ONTOLOGI, EPISTEMOLOGI DAN AKSIOLOGI PENDIDIKAN ISLAM - Fawwaz Noor Amirul Huda (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2021)
Philosophy includes five branches of discussion, namely: logic, etestics, ethics, politics and metaphysics. The purpose of this research is to reveal how the meaning and function of the philosophy of science in Islamic education This research is a qualitative research that focuses on library research, using compare, summarize and synthesize approaches. In data source research there are two namely, primary data source and secondary source. The primary sources are books on the philosophy of Islamic education, while the secondary source is books related to the writing of this article. The method used in this research is philosophical analysis method. The results showed that education is the design of philosophy, while philosophy cannot be done without the existence of high science that is only obtained from the process of education. Whereas an advance in science would be easily destroyed if it had ruled out philosophy.